STRATEGI PEMBELAJARAN MENGAJI MENGGUNAKAN METODE UMMI PADA SISWA LOW ABILITY LEARNERS: STUDI KASUS SISWA KELAS X DI SMA MUHAMMADIYAH 3 TULANGAN - M. Ridho Naufal Amien; Dzulfikar Akbar Romadlon (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the strategy of learning to recite the Al-Qur'an using the Ummi Method for low ability learners at SMA Muhammadiyah 3 Tulangan, focusing on method modification, obstacles, and the impact of its implementation. Utilizing a qualitative approach with an intrinsic case study design, data were gathered through participant observation, in-depth interviews with Quranic teachers and students, and the documentation of student achievement records. The results indicate that the primary strategies implemented include pure classical reading and listening techniques and the direct method, both of which emphasize the intensive repetition of the Rost rhythm. Teachers integrated the scaffolding theory through robust individual guidance to elevate the capabilities of students scoring below the Minimum Mastery Criterion (KKM). Despite facing constraints such as students' low cognitive memory and a lack of support for practicing at home, this method proved effective in improving makhraj accuracy and reading fluency, while simultaneously fostering spiritual motivation and psychological comfort among adolescents. The novelty of this study lies in the formulation of a modified Ummi Method model that blends psychological-spiritual scaffolding specifically tailored to overcome Al-Qur'an literacy barriers in senior high school adolescents—a locus that remains rarely explored compared to mass implementation in childhood age ranges.